PATTERN OF ADVERSE DRUG REACTIONS AND ITS MANAGEMENT IN FEMALE CANCER PATIENTS IN A PRIVATE HOSPITAL IN TELANGANA, INDIA - P, Kishore; Meghana, G; Reddy, B. Pratap; Raghavaiah, K V; kumar, D Sudheer (Asian Journal of Pharmaceutical Research and Development, 2018)
ABSTRACT Chemotherapy and radiation are one of the important components of treatment for many cancers. Anti-neoplastic agents are used with caution due to their high toxicity and narrow therapeutic window. Studies describing pattern of adverse drug reactions in cancer chemotherapy and radiation therapy patients are less in India. This study aims to evaluate the pattern of ADR’s due to cancer chemotherapy and radiation therapy in hospitalized patients and to assess the causality and severity of these reactions in Telangana state, India. This was a prospective observational study conducted in a private hospital in Telangana region from January to august. Two thousand three hundred and forty two ADR’s were recorded from 254 patients. Most common ADR’s were vomiting (10.7 %), nausea (10.7 %) and fatigue (10.7 %). Majority of the ADR’s (53.5 %) were affecting the Gastro-intestinal system. Naranjo scale for causality assessment showed 54.3 % of the reaction to be “definite”, 36.8 % to be “probable”. Modified Hartwig and Siegel scale for severity showed most reaction (84.1 %) to be of “moderate level”, while 13.3 % of reactions were of “mild level”. There is an immediate need to create awareness among health care professionals regarding the importance of the pharmacovigilance system. Use of preventive measures is to be enhanced in order to reduce the incidence and severity of ADR’s. This study showed most ADR’s are preventable with effective ADR monitoring. Keywords: Adverse drug reaction (ADR), ADR monitoring, Pharmacovigilance, chemotherapy, radiation therapy.